Purificação da dextranasacarase de L. mesenteroides FT045B, produção de dextrana de massa molar média controlada, produção de ácido ascórbico α-glicosídeo e do composto bromo-dextrana - Vettori, Mary Helen Palmuti Braga [UNESP] (2014)
Development on technological applications of dextran produced by the bacterium Leuconostoc mesenteroides FT045B. Enzyme dextransucrase was purified with polyethyleneglycol (PEG), followed by gel filtration chromatography. After analysis by SDS-PAGE revealed that the enzyme presents dextransucrase FT045B molar mass of approximately 136 kDa. Results obtained by analysis of variance (ANOVA) showed that the experiment with 10% PEG 1500 and 20% PEG 4000 showed better dextransucarase enzyme purification. It was confirmed that the purified enzyme is a glycosyltransferase, but not a fructosyltransferase by activity on acrylamide gel under non denaturants conditions. The α-glycoside ascorbic acid was synthesized by transglycosylation reaction catalyzed by dextransucarase previously purified, and structurally characterized after purification by mass spectrometer ESI-MS. A central compositio design was also purified with dextransucarase performed to optimize the conditions of temperature, concentration and enzyme activity of sucrose to produce dextran of molecular weight controlled, and the optimal point obtained was set at 4.27% Tween 80 and 1,83g of agitation. The compound Bromo-dextran was synthesized by the reaction of acetylation followed by bromation of dextran, and purification with ethanol, drying and identification